Tinjauan Yuridis Pemidanaan terhadap Anak Dalam Tindak Pidana Narkotika - Rauf, Sofyan; Rosmaidar, Rosmaidar (Jurnal Ilmiah Dikdaya, 2022)
Narcotics abuse has long been a serious problem faced by the Indonesian government. Narcotics are also used as a tempting wetland for dealers because they provide enormous profits from the sale of these illicit goods. Narcotics abuse in Indonesia has recently become more widespread and does not only attack adults but children and the next generation of the nation are also targeted for narcotics distribution, some of them are even made into dealers. The purpose of this research is to find out the Judge's Racitio Recidendi in deciding case number 4/pid.sus.-anak/2021/Pn unaaha. The type of research conducted in this research is normative, where this research does not only cover statutory regulations and legal materials in the library. The results of the study can be concluded that the Juridical Analysis of Recidendi Ratio Judges in deciding case Number.4/Pid.sus.anak/2021/Pn unaaha in dealing with cases of criminal possession of narcotics against the law generally have considered mitigating and aggravatingThe child defendant has considered the provisions of Article 2 and Article 71 of Law No. 11 of 2012 and has also considered the community research report. The judge still imposes a sentence, the judge in this decision only uses the theory of punishment, namely the theory of deterrence by imposing a coaching sentence outside the institution, in this case placing the child perpetrator in the Special Child Special Institution (LPKA) class II Kendari for 3 (three) years, and following guidance, education and job training for 3 (three) months.